Perbandingan Regulasi Penanaman Modal Indonesia dan Singapura - Fadhlan Dwi Juliardi Albana; Zulfikri Toguan; Rahmansyah Siregar (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Foreign investment is a crucial factor in driving economic growth because it provides not only capital but also technology, skills, and access to global markets. This study aims to compare investment regulations in Indonesia and Singapore and to analyze the factors that support and hinder the flow of foreign direct investment (FDI). The method used in this study is a normative approach with a comparative legal analysis, drawing from legal documents, legislation, bilateral agreements, and academic literature from 2020 to 2026. Data were analyzed using qualitative descriptive methods to evaluate differences in regulations, licensing procedures, legal protections, and compliance with international standards. The results indicate that Singapore holds a significant advantage over Indonesia in terms of legal certainty, transparency of licensing procedures, and regulatory openness, making it more attractive to foreign investors On the other hand, Indonesia still faces challenges in the form of complex bureaucracy, regulatory inconsistencies, and restrictions in several strategic sectors. These factors significantly affect investor interest and competitiveness at the regional level. This study recommends that Indonesia simplify investment procedures, harmonize national regulations, and strengthen legal protections including the implementation of bilateral P4M agreements to enhance the appeal of foreign investment in the region.